A Novel Control Algorithm for Self Adjusting Dynamic Voltage Stabilization Scheme - Ozkop, E.; Sharaf, A. M.; Altas, I. H. (Elektronika ir Elektrotechnika, 2014)
The paper presents a novel FACTS based Dynamic Voltage Stabilization Scheme (DVSS) for Distribution/Utilization Grid systems. The FACTS device is controlled by using multi loop error driven dynamic control strategies. In order to do this Matlab/Simulink/Simpower Software with GUI interface has been used for all digital simulation models of the all sub system components, DVSS, and the control algorithms. The proposed FACTS-DVSS is controlled by using a multi-loop decoupled controller scheme with either PI, fuzzy logic or sliding mode controllers. The novel FACTS device with flexible controllers is validated under system and load excursions and is proven to be effective in enhancing power quality and electric energy utilization as well as effective dynamic voltage stabilization, transient voltage excursions and inrush current conditions. DOI: http://dx.doi.org/10.5755/j01.eee.20.3.2827